Answer:
y = -3/2x + 1
Explanation:
Perpendicular lines' slope will have the negative reciprocal of the other one's slope.
First, put 2x-3y = 6 into slope - intercept form, so it would be:
![-3y = -2x+6\\y = (2)/(3)x - 2](https://img.qammunity.org/2022/formulas/mathematics/high-school/c0p55xcclelmkxb6zs2jtbiojwun6yk318.png)
This means that the slope of that line is 2/3, so the slope of the perpendicular line would have to be -3/2.
Then, you can put this into point-slope form, so it would look like:
y - 4 = -3/2 (x + 2)
![y = -(3)/(2) x - 3 + 4 \\y = -(3)/(2)x + 1](https://img.qammunity.org/2022/formulas/mathematics/high-school/5jbrq0qvzyxb83duk67yq8r074ew72z1ff.png)